Indo-European nasal presents between phonology and morphology (Atti del Sodalizio Glottologico Milanese, 2014)
This study aims at focusing on some morpho-phonological problems which affect nasal presents in Indo-European languages. My proposal does not want to be exhaustive, as the theme offers several difficulties in any perspective one can treat it. In detail, I deal with some asymmetries between IE *-nos formations in the nominal domain, and the verb stems built through nasal morphology, and I argue for an etymological relation between them. KEYWORDS: Indo-European, verbal morphology, nasal infixes, word-formation, reconstruction